MAKNA SIMBOL WAYANG KEBO DALAM KAIN TENUN GRINGSING DESA TENGANAN PEGRINGSINGAN KARANGASEM BALI - Apriliani, Ni Wayan; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT Gringsing Fabric is a woven fabric with double tied model which is very unique. This Fabric only exists in three countries India, Japan and Indonesia, in Tenganan Pegringsingan village. This study attempts to find the symbol meaning which is available on the Gringsing Wayang Kebo woven fabric in Tenganan Pegringsingan. Symbolsin the form of motives and color which contained in the Gringsing Wayang Kebo woven fabric, will be analyzed using the Roland Barthes Semiotic Theory in which there are denotation, connotation and myth in it. The results showed that there is symbol meaning in the motive and the color of the Gringsing Wayang Kebo woven fabric, which contained the balanced life meaning in Tenganan, in which the people love and respect each other without differentiate caste and gender.Tenganan people have beliefs of Rwa Bhineda. Keywords: Meaning of symbols, Semiotics, Woven Fabric, Gringsing Wayang Kebo Pattern